Comparison of vertical jump and sprint performances between 3 × 3 and 5 × 5 elite professional male basketball players - Cabarkapa, Dimitrije; Johnson, Quincy R.; Aleksic, Jelena; Cabarkapa, Damjana V.; Philipp, Nicolas M.; Sekulic, Marko; Krsman, Darko; Trunic, Nenad; Fry, Andrew C. (Frontiers in Sports and Active Living, 2024)
Given its fast-growing popularity and unique on-court competitive demands, 3x3 basketball has captured a considerable amount of attention over recent years. However, unlike research focused on studying 5x5 basketball players, there is a lack of scientific literature focused on examining countermovement vertical jump (CMJ) and sprint performance characteristics of 3x3 athletes. Thus, the purpose of the present study was to compare force-time metrics during both eccentric and concentric phases of the CMJ and acceleration and deceleration capabilities between 3x3 and 5x5 top-tier professional male basketball athletes. Ten 3x3 and eleven 5x5 professional basketball players volunteered to participate in the present study. Upon completion of a standardized warm-up, each athlete performed three maximum-effort CMJs, followed by two 10 m sprints. A uni-axial force plate system sampling at 1000 Hz was used to analyze CMJ force-time metrics and a radar gun sampling at 47 Hz was used to derive sprint acceleration-deceleration measures. Independent t-tests and Hedge's g were used to examine between-group statistically significant differences (p<0.05) and effect size magnitudes. The findings of the present study reveal that 3x3 and 5x5 professional male basketball players tend to display similar neuromuscular performance characteristics as no significant differences were observed in any force-time metric during both eccentric and concentric phases of the CMJ (g=0.061-0.468). Yet, prominent differences were found in multiple measures of sprint performance, with large effect size magnitudes (g=1.221-1.881). Specifically, 5x5 basketball players displayed greater average and maximal deceleration and faster time-to-stop than their 3x3 counterparts. Overall, these findings provide reference values that sports practitioners can use when assessing athletes' CMJ and sprint performance capabilities as well as when developing sportspecific training regimens to mimic on-court competitive demands.